SOME QUALITY CHARACTERISTICS AND INDIVIDUAL PHENOLIC COMPOUNDS OF EUROPEAN PEAR CULTIVARS - Öztürk, Ahmet; Desmirsoy, Leyla; Demirsoy, Husnu; Ozturk, Sema (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Pear fruits are an important source of secondary plant metabolites and one of the major sources of dietary phenolic compounds. Materials and Methods: The aim of this study was to determine the individual phenolic compounds and some chemical characteristics of the flesh and peel of the fruit in the four pear cultivars. The phenolic composition of these pear cultivars was determined by high performance liquid chromatography with diode array detection (HPLC-DAD). Results: The fruit flesh firmness ranged from 35.2 to 85.8 N in the pear cultivars. The soluble solids content was higher in the flesh, while titratable acidity, vitamin C, individual phenolic compounds and total phenolics were generally higher in the peel. Arbutin, chlorogenic acid and epicatechin were detected as major phenolic compounds in the peel and flesh of pear fruits. Arbutin, chlorogenic acid and epicatechin of the flesh and peel ranged from 834.8 to 937.9 mg kg-1; from 332.1 to 460.7 mg kg-1; and from 77.2 to 104.0 mg kg-1 for ‘Seckel’ pear fruits, respectively. The highest total phenolics were found to be in the peel and flesh of the ‘Flemish Beauty’ pear fruits. Conclusion: Because of the higher level of antioxidant components in the peel of pear fruits (all phenolic compounds and vitamin C) consumption of unpeeled pears, after proper washing, is recommended to maximize the dietary benefit.